Synthesis of new pyromellitdiimde homo and copolymers containing (N-allyl methylol) component - Al-Azzawi, Ahlam Marouf; Mohammed Ali, Mustafa Dawood (International Journal of Psychosocial Rehabilitation, 2020)
In this work six new pyromellitdiimde polymers containing (N-allyl methylol) component were synthesized through performing many steps. The first step involved treatment of pyromellitic anhydride with urea producing N-unsubstituted pyromellitdiimide (1) which inturn was converted in the second step to bis(N-methylol) pyromellitdiimide (2) via reaction with formaldehyde .Treatment of (2) with allyl bromide in the third step afforded bis (N-allyl methylol) pyromellitdiimde (3). Subsequently the new monomer (3) was introduced in free radical homo and copolymerization producing the target new polymers (4-9) which exhibit improved properties.